INCREASING THE EFFICIENCY OF THE ROOF PURLIN SYSTEM (Collection of scientific works «Modern structures of metal and wood», 2021)
In the article, the authors consider one of the ways to solve the problem of reducing metal consumption and increasing the efficiency of metal structures by choosing an effective static scheme. The choice of the appropriate scheme is carried out for the most common elements of metal structures - beams, which also include roof purlins. To cover the industrial building of the seaport, discontinuous and continuous stringer systems are  being  developed  and  their  efficiency  is  analyzed  in  terms  of  metal  consumption  and  labor intensity.